Enzymes of the Shikimic Acid Pathway Encoded in the Genome of a Basal Metazoan, Nematostella vectensis, Have Microbial Origins - Starcevic, Antonio; Akthar, Shamima; Dunlap, Walter C.; Shick, J. Malcolm; Hranueli, Daslav; Cullum, John; Long, Paul F. (Proceedings of the National Academy of Sciences - PNAS, 2008)
The shikimic acid pathway is responsible for the biosynthesis of many aromatic compounds by a broad range of organisms, including bacteria, fungi, plants, and some protozoans. Animals are considered to lack this pathway, as evinced by their dietary requirement for shikimate-derived aromatic amino acids. We challenge the universality of this traditional view in this report of genes encoding enzymes for the shikimate pathway in an animal, the starlet sea anemone Nematostella vectensis. Molecular evidence establishes horizontal transfer of ancestral genes of the shikimic acid pathway into the N. vectensis genome from both bacterial and eukaryotic (dinoflagellate) donors. Bioinformatic analysis also reveals four genes that are closely related to those of Tenacibaculum sp. MED152, raising speculation for the existence of a previously unsuspected bacterial symbiont. Indeed, the genome of the holobiont (i.e., the entity consisting of the host and its symbionts) comprises a high content of Tenacibaculum-like gene orthologs, including a 16S rRNA sequence that establishes the phylogenetic position of this associate to be within the family Flavobacteriaceae. These results provide a complementary view for the biogenesis of shikimate-related metabolites in marine Cnidaria as a "shared metabolic adaptation" between the partners.